Pelatihan Editing Video Komisi Senior GKI Pondok Tjandra Indah Sidoarjo: Berdamai dengan Teknologi - Siswo Martono; Hardman Budiardjo; Sulistiowati, Sutikno; Martinus Sony Erstiawan (Ekobis Abdimas, 2025)
The rapid development of digital technology has created a significant digital divide among the elderly, including the senior members of GKI Pondok Tjandra Indah Sidoarjo, who feel left behind and dependent on the younger generation for digital activities. Despite this, they are highly motivated to be independent in expressing themselves through social media. To address this issue, GKI PTI Sidoarjo initiated a video editing training program using the CapCut application. The purpose of this activity is to empower senior congregants with a basic understanding of video editing that is easily accessible, thus increasing their confidence and digital independence. The expected benefits of the activity are to reduce dependence on others, encourage positive self-expression through social media, and realize the concept of “Making Peace with Technology” for senior congregations. The training was held for two days using the direct instruction method, which includes the stages of preparation (needs identification, basic skills analysis, material preparation, promotion), implementation (basic introduction to hands-on practice), and evaluation (pre-test and post-test). The results of the activity showed significant improvement in the technical skills of using CapCut (cropping, adding text/music, creating simple videos) and positive changes in participants' attitudes and confidence towards technology. The majority of participants (100%) realized the positive benefits of technology and more than half felt more independent. Conclusions show that the training was highly effective in bridging the digital divide and increasing self-reliance, although the limited duration and varying abilities of participants require follow-up such as self-paced modules and learning communities.